1999
DOI: 10.3354/meps186105
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the chemical characteristics of oceanic DOM and extracellular DOM produced by marine algae

Abstract: ABSTRACT-The chemical characteristics of extracellular high molecular weight (HMW) dissolved organic matter (DOM) from 3 species of marine phytoplankton were compared to HMW D O M in seawater. Thalassiosira weissflogii, Emiliania huxleyi and Phaeocystis sp., were grown in nutnent ennched seawater that had been previously ultrafiltered to remove HMW DOM. The extracellular HMW DOM produced in these cultures was isolated by ultrafiltration and charactenzed using nuclear magnetic resonance (NMR) spectroscopy, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
178
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(198 citation statements)
references
References 24 publications
15
178
1
Order By: Relevance
“…Because Alcian Blue reacts with acidic sugars, an 'Alginic Acid equivalent' carbon content can be interpreted as the carbon content of the acidic sugars (monomers) within the polysaccharide. To date the acidic sugar content of TEP is not known, but since the neutral sugar composition of TEP is similar to that of polysaccharides released by marine phytoplankton (Mopper et al, 1995;Aluwihare and Repeta, 1999), it can be suggested that the acidic sugar fractions are of comparable magnitude also. For example, 20% of the total sugar content of polysaccharides released by E. huxleyi are represented by the acidic sugar dgalacturonic acid (De Jong et al, 1979).…”
Section: Relationship Between Tep and Pocmentioning
confidence: 99%
“…Because Alcian Blue reacts with acidic sugars, an 'Alginic Acid equivalent' carbon content can be interpreted as the carbon content of the acidic sugars (monomers) within the polysaccharide. To date the acidic sugar content of TEP is not known, but since the neutral sugar composition of TEP is similar to that of polysaccharides released by marine phytoplankton (Mopper et al, 1995;Aluwihare and Repeta, 1999), it can be suggested that the acidic sugar fractions are of comparable magnitude also. For example, 20% of the total sugar content of polysaccharides released by E. huxleyi are represented by the acidic sugar dgalacturonic acid (De Jong et al, 1979).…”
Section: Relationship Between Tep and Pocmentioning
confidence: 99%
“…This has been shown for benthic diatoms, whose extracellular carbohydrate production has been extensively studied over the last few years (Underwood & Paterson, 2003;Bellinger et al, 2005Bellinger et al, , 2009Abdullahi et al, 2006). Monosaccharides commonly found in extracellular carbohydrates released by marine phytoplankton include aldohexoses (glucose, galactose and mannose), aldopentoses (arabinose and xylose), deoxysugars (fucose and rhamnose), uronic acids (glucuronic acid) and amino sugars (Aluwihare et al, 1997;Biersmith & Benner, 1998;Aluwihare & Repeta, 1999;Magaletti et al, 2004;Kragh & Søndergaard, 2009). The monosaccharide composition of the surface ocean is similar to the monosaccharide composition of phytoplankton extracellular release, indicating that phytoplankton are a major source of Bars show mean + SD (n = 3 replicate cultures).…”
Section: Carbohydratesmentioning
confidence: 99%
“…In the present study, we show that DCNS comprise upwards of 50% of coral exudates and a smaller but still significant fraction of macroalgal exudates (8-33%; Table 3). The DCNS fraction of DOC is clearly not the only material exuded by algae and coral, as uronic acids, proteins, amino sugars and lipids have all been detected in the tissue and DOM of algae (Percival, 1979;Jensen, 1993;Aluwihare and Repeta, 1999;Wada et al, 2007;Anastasakis et al, 2011) and the tissue and mucus of coral (Meikle et al, 1988;Coffroth, 1990;Wild et al, 2010). However, the composition of the exuded DCNS did differentiate the four exudates from both experimental controls and the ambient waters (Figure 1a), and portions of the DCNS pool were preferentially and differentially utilized by bacterioplankton among the treatments (Figures 1c and d; Tables 2 and 3), suggesting that it is a meaningful proxy for differences in the overall character of the DOM exuded by benthic macroorganisms on coral reefs.…”
Section: Macroalgal and Coral Dom Exudate Composition And Bacterioplamentioning
confidence: 99%